Unfinished Treatise by Jevons (Quarterly Journal of Economics, 1887)
Unfinished Treatise by Jevons Get access The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 65–66, https://doi.org/10.1093/qje/2.1.65-a Published: 01 October 1887